O021 A Question of Stability. (30th June 2016) - Patel, Hemanti; Schembri, Gabriel; Sultan, Binta; Ison, Catherine
Abstract : Background/introduction: Urines to be tested by the APTIMA Combo 2 (AC2) are added to a collection tube containing preservatives to ensure stability of the nucleic acid for testing within 24 hours of collection. Home collected urines are often collected in containers without preservative to avoid the patient manipulating the sample. Aim(s)/objectives: An investigation was undertaken to determine the stability of gonococcal and chlamydial nucleic acids within neat urine stored in different conditions over a period of 25 days to provide evidence of the stability of the nucleic acid prior to testing. Methods: To mimic collection in a home setting and differing nucleic acid loads within clinical specimens, uninfected urine was inoculated with different concentrations of chlamydial (from cell culture) and gonococcal (from bacterial culture) nucleic acid. Aliquots of the urine were removed on eight occasions over 25 days, added to collection tubes and tested either on the Hologic Panther system to determine presence of RNA or, following DNA extraction, using in-house PCRs to determine DNA load. Results: Chlamydial RNA and DNA remained stable for over three weeks when either refrigerated or stored at room temperature. Gonococcal RNA was detectable up to three weeks if refrigerated and two weeks if stored at room temperature. GC DNA was detectable for 18 days if refrigerated and for 11 days if stored at room temperature. Discussion/conclusion: Chlamydial and gonococcal nucleic acids are stable in urine before addition to preservatives for longer than recommended by the manufacturer, enabling more flexibility for home collected samples.